Uwarunkowania i kierunki rozwoju polskiego rynku motoryzacyjnego na tle zachodzących procesów integracyjnych - Radkowska, Jolanta; Radkowski, Krzysztof (The Automobile Market in Poland - Conditions and Directions of Changes Concerning the On-going Process in Integration, 2007)
Thanks to the dynamic development of the 1990's, including investments by the world's major automobile corporations, the auto industry has become one of the most modern sectors in Polish industry. It has a substantial influence on the economic situation and the employment rate in other production sectors as well as rendering services to the needs of the auto market. This article presents the conditions and trends in the changing auto market in Poland regarding the continuing process of integration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 187-195